The influence of imagery on the accuracy of men's volleyball athletes' jump services - Laksana, Tegar Pramudia; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Jurnal Patriot, 2024)
Problems: Problems in study This is Athletes often pay little attention to their psychological training methods, because they think that service is not that important, therefore imagery training is very important and is the solution in this research. Purpose: Internal goal study This is to know influence exercise imagery against accuracy service jump volleyball athlete​ son. Methods: Research This use method quantitative with approach experiment one group pre-test post-test design. Result: Research results show that exercise imagery give influence to accuracy volleyball athlete's service jump son by 26%. Conclusion: The implementation of appropriate and consistent imagery training has been proven effective in enhancing the accuracy of jump serves among male volleyball athletes. It is therefore recommended that volleyball coaches incorporate sustained imagery training into their training programs.